Evaluasi RME Rawat Jalan Menggunakan Metode EUCS di RSUD Ngudi Waluyo Wlingi - Wijayanti, Rossalina Adi; Rohman, Nur Cholis Abdul; Rachmawati, Ervina; Rahagiyanto, Angga (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2025)
Obstacles were found in the development of RME at Ngudi Waluyo Wlingi Regional Hospital, namely that there were registration form items that were not used, x-ray results sometimes did not appear resulting in doctors looking at the printed results, and there was no RME user manual. This study aims to evaluate outpatient RME using the EUCS method. This research is a quantitative descriptive study using the end-user computing satisfaction method. The total sample was 54 respondents using the Lemeshow formula. The data collection technique is by distributing questionnaires. User satisfaction analysis, namely the results of respondents' answers, is calculated for each variable, namely content, accuracy, format, timeliness, ease of use. The results are compared between expectations and the reality received by the user. Users are very satisfied if reality is greater than expectations. Users are satisfied if reality is the same as expectations. Users are dissatisfied if expectations are greater than reality. The research results showed that 38.89% of respondents were dissatisfied with content, 37.04% of respondents were dissatisfied with accuracy, 27.78% of respondents were dissatisfied with format, 29.63% of respondents were dissatisfied with timeliness, there were 42, 59% of respondents were not satisfied with ease of use. The suggestions given are for Ngudi Waluyo Wlingi Regional Hospital to review the output produced by RME, add validation warnings when input duplication occurs, develop the RME interface, and create a manual book for using RME.